THE INFLUENCE OF MOTIVATION ON BUDGET GOAL COMMITMENT THROUGH THE LEVEL OF PARTICIPATION IN BUDGETING AS A MEDIATOR - Erlandiani, Amanda Yunne; Prayogo, Enny (Indonesian Journal of Accounting and Governance, 2023)
This study aims to investigate and analyze the influence of motivation, consisting of twodimensions, in affecting budget goal commitment through the level of participation in budgeting as amediator. The two dimensions of motivation referred to are intrinsic motivation and controlledextrinsic motivation. Data were collected through survey-based research by distributing questionnairesto lower-level managers in the garment and textile manufacturing sector in Bandung. To analyze dataand test mediation, this study used a structural equation model (SEM) with the alternative partial leastsquares (PLS) method. The results of this study suggest that both intrinsic motivation and controlledextrinsic motivation have a positive effect on the level of participation in budgeting. In addition, thelevel of participation in budgeting mediates the influence of each motivation dimension on budget goalcommitment. Companies can take action to improve budget goal commitment by managing motivationthat will impact the level of participation in budgeting.